Fire, Heroes and the Cosmic: Aesthetic Resonances of Fire-walking in Northern Greece - Kondos, Vivienne (The Australian journal of anthropology, 2000)
In the Greek village of Mavrolefki in Thrace, a small number of women and men. about ten in number, once a year, on the feast day of St. Constantine, undertake a series of rites, ranging from dancing to the icons, blood sacrifice, to the most spectacular fire-walking (pyrovasia). It is the last which brings spectators from all over Greece and further afield. The principal participants, however, are known as the anastenarides (shakers, tremblers). Several concerns are addressed in the paper. Given the peculiar mix of proceedings, the first is to lay out the components of the affair, asking what's going on? Furthermore, there are the conceptual issues. What aesthetic is being implicated? What emotions are being brought into play? What does the event amount to? In addressing such questions the paper draws on certain aesthetic formulations of the Hindu rasa theory.